ANALISIS ETNOMATEMATIKA PADA POLA BATIK TANAH LIEK KHAS MINANGKABAU TERHADAP MATERI TRANSFORMASI GEOMETRI KELAS XI SMA/MA - Marisa; Rahman, Antoni; Arif, Muhammad (PGRI Provinsi Riau, 2021)
This research is motivated by the problem of the lack of mathematics learning that uses examples of local culture, for example learning Transformation Geometry through the Tanah Liek batik motif in Minangkabau. As a result, students tend to feel bored because the activities carried out are monotonous just sitting, listening and copying. The aim of this research is to find out the topic of geometric transformation in the Tanah Liek batik culture in Minangkabau and to find out the use of the Tanah Liek batik context in Geometry Transformation learning. This type of research is qualitative with an ethnographic approach. Which uses data collection techniques through in-depth interviews, participant observation and documentation studies. Which is located at the Tanah Liek Batik House and Loempo Batik House. The theoretical basis for this research is the ethnomathematics of Minangkabau typical Tanah Liek batik on Geometry Transformation material for class XI SMA/MA. The results and discussion of this research relate the material of Geometric Transformation. Which is associated with the typical Minangkabau Tanah Liek batik pattern. In accordance with previous relevant research that ethnomathematics has a relationship with mathematics learning materials. Thus, this research can produce an initial study on the ethnomathematics of Minangkabau typical Tanah Liek batik on Geometry Transformation material for class XI SMA/MA.